Development of the Integrated Flood Hazard Index (FHI) for a Multi-Criteria Assessment of Mudflow Hazard (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents a comprehensive approach to the quantitative assessment and mapping of debris-flow hazard at the regional scale (using Samarkand Region as a case study) through the development of an integrated Flood Hazard Index (FHI). The index is constructed using a Multi-Criteria Analysis (MCA) framework and incorporates six key thematic layers: precipitation intensity (CHIRPS), flow accumulation (HydroSHEDS ACC), terrain slope (SRTM), distance to surface water bodies (JRC Global Surface Water), vegetation index (MODIS NDVI), and global land-cover data (ESA WorldCover). Data processing was carried out within the Google Earth Engine (GEE) environment, while layer integration was performed using normalization procedures and the Weighted Linear Combination (WLC) technique. The resulting FHI map delineates four hazard classes (very low to high) and reveals the spatial concentration of high hazard levels in the mountainous and piedmont catchments of the Middle Zarafshan. The methodological principles and datasets employed in the study are aligned with contemporary practices in satellite remote sensing and GIS-based hazard assessment.